A novel immunopathological association of IgG4-RD and vasculitis with Hashimoto's thyroiditis. (1st March 2016) - Minamino, Hiroto; Inaba, Hidefumi; Ariyasu, Hiroyuki; Furuta, Hiroto; Nishi, Masahiro; Yoshimasu, Takashi; Nishikawa, Akinori; Nakanishi, Masanori; Tsuchihashi, Shigeki; Kojima, Fumiyoshi; Murata, Shin-ichi; Inoue, Gen; et al.
Summary: A 73-year-old man with Hashimoto's thyroiditis (HT) suffered from purpura on the lower legs. He was diagnosed with IgG4-related disease (IgG4-RD) with serum IgG4 elevation and dacryo-sialadenitis confirmed histologically. Serum Th2 and Treg cytokines, interleukin 7 (IL7), IL8 and Th2 chemokine levels were elevated, while skewed Th1 balance was seen in fluorescence-activated cell sorting (FACS). Therefore, preferential Th1 balance in HT appeared to be followed by IgG4-RD characterized with Th2 and Treg polarization. The commencement of steroid therapy dramatically exacerbated clinical manifestations including IgG4-RD-associated HT. The measurement of cytokine and chemokine levels as well as FACS analysis in the development of IgG4-RD seemed to be beneficial. In conclusion, an innovative association of HT, IgG4-RD and vasculitis was observed. This report also offers novel diagnostic and therapeutic approaches for IgG4-RD. Learning points: Recently, a subtype of HT has been considered to be a thyroid manifestation of IgG4-RD, although the etiology of IgG4-RD is not established yet. Immunologically a close association between HT and vasculitis was reported. Leukocytoclastic vasculitis is a rare skin presentation of IgG4-RD. In the current case, during the course of HT, IgG4-RD and leukocytoclastic vasculitis occurred; thus, innate immunity and acquired immunity seem to be involved in the development of IgG4-RD. The measurement of cytokine and chemokines appeared to be beneficial in the development of IgG4-RD. Remarkably, effectiveness of steroid therapy for HT suggested presence of IgG4-RD-associated HT. Therefore, this report highlights the pathogenesis of IgG4-RD and proposes novel therapeutic mechanisms. Clinicians should pay attention to the development of IgG4-RD and vasculitis during long course of HT.